BORJUIS JAWA: TRANSFORMASI SOSIAL DI TENGAH KOLONIALISME ABAD XIX-XX - Irvan Tasnur; Naufal Raffi Arrazaq; Fitra Widya Wati (Yayasan Literasi Sains Indonesia, 2025)
This study examines the emergence and development of the local bourgeoisie in Java in the 19th to 20th centuries. The main focus of the study is the transformation of the social class structure due to the implementation of liberal economic policies by the Dutch colonial government. The aim is to understand how the concept of